Ni-Biochar dari limbah daun kelapa sawit sebagai fotokatalis berbiaya rendah untuk degradasi zat warna metil jingga - Dwiki Ramanda, Galih; Is Fatimah; Suresh Sagadevan; Mohd Rafie Bin Johan (EKSAKTA: Journal of Sciences and Data Analysis, 2025)
Photocatalytic oxidation is one of the methods in the advanced oxidation process. The method depends on several factors to be effective in application, one of these is the cost-effectivity and sustainability. The intent of this research work is to synthesize low-cost photocatalyst by using waste: palm leaves ash. Lignocellulosic as a structural compenent found in palm leaves has the potential for various applications, including as a catalyst for wastewater treatment. The Ni-biochar (Ni-BC) photocatalyst based on nickel nanoparticles was synthesized by using palm leaves under pyrolysis method on two varied Ni content; 10 and 30 % wt to get Ni10-BC and Ni30-BC, respectively. Various characterization techniques consist of XRD, SEM, and VSM were conducted, meanwhile the photocatalytic activity for methyl orange photodegradation was employed as activity testing. Results showed that single nickel nanoparticles dispersed on biochar structure are appeared by XRD measurement. The porous structure of materials is derived, with the magnetism of 9.64 emu/g and 3.87 emu/g for Ni content of 10 and 30 % wt., respectively. The fabricated Ni-BC samples showed excellent photoactivity represented by 74.73 and 50.01% of the degradation efficency towards methyl orange by Ni10-BC and Ni30-BC, respectively. A persuasive mechanism and kinetics are well presented. The kinetics study expressed the fitness of the degradation that follow pseudo-first order kinetics.